Cost, performance and energy consumption of 5G fixed wireless access versus pure fiber-based broadband in Sweden - Jie Li; Marco Forzati (International Telecommunications Society (ITS), 2020)
This work aims to contribute to the debate on the fixed wireless versus fixed line broadband access solutions by focusing on scenarios offering Gbps level broadband access. More specifically, we performed a techno-economic analysis on the cost, performance (in the term of download speed) and energy consumption of optical fiber versus 5G fixed wireless access (FWA) based solutions over a 10-year perspective. The study is based on the case in Sweden in order to achieve one of the Swedish government's 2025 broadband goals that 98% of Swedish households and workplaces should have at least 1 Gbps broadband access. Alongside with the pure fiber-based solution, 3 FWA-based scenarios using existing commercial macro cells, newly installed mmWave small cells, and hybrid macro and small cells, are evaluated. Based on the findings in this work we conclude that: 1) The pure fiber-based solution should be the "default" choice in order to achieve the Swedish government's 2025 broadband goal to reach 98% of Swedish households and workplaces with at least 1 Gbps broadband access; 2) Even though FWA using mmWave small cells is potentially capable of achieving the 1 Gbps @ 98% goal, the trade-off will be the high total cost levels and more energy consumption. In addition, the end user experience is subject to variations of whether and environmental conditions, and the distance to the network antenna; 3)FWA using existing commercial macro cells alone is not capable to reach the 1 Gbps @ 98% goal, despite the estimated relatively low cost. In addition, the estimated energy consumption level is also significantly higher than the pure fiber-based solution. To the best of our knowledge, this is the first-time reported techno-economic study on comparing 5G FWA with pure-fiber-based broadband access.
Keywords: 330; 5G; fixed wireless access; fiber broadband; techno-economic analysis